Theodore Sedgwick correspondence - Sedgwick, Theodore, 1746-1813.
ALS written by Sedgwick to Benjamin Bourne regarding Congressional representation, assumption of state debt, government relations with Indians, and other political matters.
Delegate to the Continental Congress, U.S. senator and representative from Massachusetts, and jurist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Bourne, Benjamin, -- 1755-1808 -- Correspondence; United States. -- Congress; Debts, Public; Indians of North America -- Government relations -- 1789-1869.; Massachusetts -- Politics and government -- 1775-1865.; United States -- Politics and government -- 1789-1797.; Delegates, U.S. Continental Congress -- Massachusetts; Jurists; Representatives, U.S. Congress -- Massachusetts; Senators, U.S. Congress -- Massachusetts